Preparation and antibacterial and antioxidant ability of β‐cyclodextrin complexes of vaporized Illicium verum essential oil. Issue 11 (26th July 2022) - Wu, Kegang; Zhang, Tong; Chai, Xianghua; He, Dong; Duan, Xuejuan; Yu, Bingying; Chen, Yongqi; Huang, Yuqiang
Abstract: Compared with traditional liquid–liquid embedding method and solid–liquid embedding method of inclusion complexes of β‐cyclodextrin (β‐CD) inclusion of essential oil to form stable properties, the gas–liquid embedding method was applied to encapsulate vaporized illicium verum essential oil (IvEO), with β‐CD as wall materials so that core and wall materials molecules are in active state during complexing process. At optimal conditions with a mass ratio of 1:10, temperature of 80°C, time of 1 h, the β‐CD‐IvEO inclusion complexes (β‐CD‐IvEO‐ICs) had an encapsulation efficiency (EE) of 84.55 ± 2.31%. Fourier transform infrared spectroscopy (FTIR) revealed the encapsulation of IvEO into inclusion complexes, differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA) demonstrated the enhanced thermal stability of IvEO after embedding. Furthermore, the reducing power and 2‐phenyl‐4, 4, 5, 5‐tetramethylimidazoline‐1‐oxyl‐3‐oxide (PTIO)‐scavenging capacity displayed certain capacity of antioxidation in a short time but stronger antioxidative activities as reaction time was extended. The diameter of growth zone (DGZ) indicated stronger antibacterial activity of β‐CD‐IvEO‐ICs against Escherichia coli, Bacillus subtilis, Staphylococcus epidermidis, and Staphylococcus aureus . Moreover, the β‐CD‐IvEO‐ICs could induce the bacteria producing more reactive oxygen species (ROS) than IvEO, resulting in bacterial death. Abstract : Compared with traditional liquid‐liquid enbedding method and solid‐liquid enbedding method of inclusion complexes of #x03B2;‐cyclodextrin (#x03B2;‐CD) inclusion of essential oil to form stable properties, gas‐liquid embedding method was applied to encapsulate vaporized illicium verum essential oil with #x03B2;‐CD (#x03B2;‐cyclodextrin) as wall materials so that core and wall materials molecules are in active state during complexing process. #x03B2;‐CD‐IvEO‐ICs showed stronger antibacterial ability against Escherichia coli, Bacillus subtilis, Staphylococcus#x00A0;epidermidis, Staphylococcus aureus.